Penerapan Fraktal dalam Desain Pusat Kerajinan Tenun Ikat Lewokluok di Kecamatan Demon Pagong Kabupaten Flores Timur - Petrus Jhon Alfred D.D; Wilarius Suri Teluma (Universitas Medan Area, 2023)
The cultural tradition of tie cloth is a typical Indonesian tradition which is the origin of the cultural ecosystem of a region. Ikat cloth has even become an integral part of traditional ceremonial ceremonies, traditional marriage ceremonies, and religious ceremonies. Tie fabrics have different motifs in each region according to the peculiarities of the region itself. Lewokluok Village is a village in East Flores Regency, which has a variety of ikat motifs. The diversity of the ikat motifs is a symbol of unifying the culture of Lewokluok village from the many tribes that inhabit Lewokluok village. The provision of an tie craft center is an effort to overcome the problems faced by tie weaving craftsmen in preserving the tie culture, promoting tie weaving, and marketing the existing tie weaving works. The craft center is a place that is used as a center for production, promotion, tourism, and cultivation activities as well as the cultural development of an area. The design of the Lewokluok tie craft center uses the application of fractals. Fractal is a geometric shape that is irregular in shape, contorted but has similarities with itself. This fractal formation uses the principle of self-similarity from the basic pattern, namely the Lewokluok tie motif which is transformed into the form of building mass. This study uses a descriptive analysis method, starting from data collection consisting of primary data and secondary data. This data is obtained from the results of observations, interviews, and documentation as well as from literature studies and comparative studies of similar objects and themes. This data is then analyzed with various alternatives to produce the final design concept. In the end, it can produce a design center for Lewokluok tie weaving according to its function and purpose and increase the potential for cultural tourism in Lewokluok by applying fractals to the shape of the building that shows the characteristics of Lewokluok tie motifs.